Demographic and clinicopathological characteristics of nonalcoholic fatty liver disease in the East-Southeastern Anatolia regions in Turkey - Bahcecioglu, IH; Koruk, M; Yilmaz, O; Bolukbas, C; Bolukbas, F; Tuncer, I; Ozercan, IH (Karger, 2006)
Objective: To identify the demographic and clinicopathological characteristics of patients diagnosed with nonalcoholic fatty liver disease (NAFLD) and the risk factors for fibrosis based on histopathological findings in East-Southeastern Anatolia regions in Turkey. Subjects and Methods: The study included a total of 93 patients diagnosed with NAFLD from 5 different centers. Histopathological findings were evaluated by dividing them into four categories using Matteoni classifications. Cases with fibrosis were further evaluated using Brunt classifications. Results: The patients with a nonalcoholic fatty liver were in the 3rd and 4th decade age groups. The mean age was 38 years, 76% of the patients were male, 85% were overweight, 37% were obese, 18% had type 2 diabetes mellitus, and 80.6% had hyperlipidemia. A multiple regression analysis showed that age, type 2 diabetes mellitus, and aspartate aminotransferase (AST) levels were linked with the severity of the disease. Of the 93 patients, 55 ( 59.1%) had fibrosis, of which 10.8% were classified as severe. The severity of fibrosis was significantly higher in obese patients. Conclusions: The risk factors for severity of NAFLD included advanced age, type 2 diabetes mellitus and serum AST level, while the risk factor for the severity of fibrosis was obesity. Copyright (C) 2006 S. Karger AG, Basel.
Keywords: nonalcoholic fatty liver disease; histopathology; fibrosis